A comparative assessment of Power-to-Fuel production pathways. (15th September 2019) - Bargiacchi, Eleonora; Antonelli, Marco; Desideri, Umberto
Abstract: As the share of intermittent renewable power generation is increasing, energy storage is expected to play a key role in ensuring efficiency, resilience and stability of energy systems. Besides reducing surplus energy curtailments and addressing the issue of seasonal storage, the implementation of some Power-to-X technologies could be an effective supporting tool to decarbonization policies. This paper aims at quantifying Power-to-X process efficiencies and assessing under which conditions they could be carbon neutral during the conversion phase from electricity to a chemical storage, particularly a hydrogen carrier. For this purpose, four synthetic fuel production chains were modelled and simulated with the software Aspen Plus: methane synthesis by means of the Sabatier process, methanol synthesis by carbon dioxide hydrogenation, ammonia production with the Haber-Bosch process and urea synthesis with the Stamicarbon C O 2 stripping process. The production pathways were compared in terms of energy and exergy efficiencies, net C O 2 emissions and specific energy consumption. Emission intensity threshold values for these technologies to be carbon neutral were also estimated. Assuming that the feed hydrogen is produced by electrolysis, the impact of an upstram electrolyzer upon the aforementioned parameters was assessed and discussed. The further processing of the produced fuels (X-to-Power) is not included in the present work. Highlights: Four synthetic fuel production chains have been modelled in Aspen Plus environment Methane production is the most efficient and carbon negative technology Urea production is the most energy intensive and carbon emitting process Power-to-Fuel technologies carbon neutrality depends on the country energy mix Emission intensity threshold values for their carbon neutrality are assessed